Enzyme-linked Immunosorbent Assay and High-performance Liquid Chromatography analysis of Ochratoxin A in Zataria multiflora and Foeniculum vulgare in Ahvaz (Iran) - Ekhtelat, Maryam (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Contamination of ochratoxin A as a nephrotoxic agent can occur in a wide range of nutrients including medicinal plants. The aim of this study was to determine the amount of ochratoxin A (OTA) on high consumption medicinal herbs of Avishan Shirazi (Zataria multiflora) and Fennel (Foeniculum vulgare) in Ahvaz (Iran) using the enzyme-linked immunosorbent assay (ELISA) and high-performance liquid chromatography (HPLC) methods and compare the results of the two methods. Materials and Methods: In this study, the amount of OTA in high consumption medicinal herbs of Avishan Shirazi and Fennel (30 specimens) was investigated using HPLC and competitive ELISA methods, which were prepared randomly from groceries. Data analysis was performed using the SPSS20 software. Results: The level of OTA measured using ELISA and HPLC was significantly lower than the limit in all samples. Furthermore, despite higher contamination of fennel in both methods, no significant difference was observed between the studied plants (P > 0.05). There was a high correlation between HPLC and ELISA in determining the amount of OTA in Avishan Shirazi (r2 = 0.937) and fennel (r2 = 0.977); however, the values of OTA measured using ELISA method was higher compared to the HPLC method. Conclusion: Due to the good association between ELISA and HPLC methods, ELISA can be used to determine the contamination of OTA in plants especially as a screening method. However, chromatography methods, such as HPLC, are required in order to eliminate possible false results especially for very low amounts of toxin.